2015
DOI: 10.1007/s00221-015-4382-x
|View full text |Cite
|
Sign up to set email alerts
|

A afferent fibers are involved in the pathology of central changes in the spinal dorsal horn associated with myofascial trigger spots in rats

Abstract: A afferent fibers have been reported to participate in the development of the central sensitization induced by inflammation and injuries. Current evidence suggests that myofascial trigger points (MTrPs) induce central sensitization in the related spinal dorsal horn, and clinical studies indicate that A fibers are associated with pain behavior. Because most of these clinical studies applied behavioral indexes, objective evidence is needed. Additionally, MTrP-related neurons in dorsal root ganglia and the spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The LTR is thought to subsequently break the vicious cycle of the MTrP circuit, decreasing pain and disability (Audette et al, 2004;Chou et al, 2014;Hong and Simons, 1998;Kuan et al, 2012). Importantly, the sensitive afferents that proliferate in the MTrP region (Hong et al, 1997a;Meng et al, 2015b), mediate both the noxious input to the spinal cord (Meng et al, 2015a) and the LTR induced through needling precise MTrP locations (Hong and Torigoe, 1994;. Resting pain intensity of the MTrP before injection has been found to be highly correlated with LTR prevalence during injection (i.e.…”
Section: Dry Needling Technique and The Localized Twitch Responsementioning
confidence: 99%
“…The LTR is thought to subsequently break the vicious cycle of the MTrP circuit, decreasing pain and disability (Audette et al, 2004;Chou et al, 2014;Hong and Simons, 1998;Kuan et al, 2012). Importantly, the sensitive afferents that proliferate in the MTrP region (Hong et al, 1997a;Meng et al, 2015b), mediate both the noxious input to the spinal cord (Meng et al, 2015a) and the LTR induced through needling precise MTrP locations (Hong and Torigoe, 1994;. Resting pain intensity of the MTrP before injection has been found to be highly correlated with LTR prevalence during injection (i.e.…”
Section: Dry Needling Technique and The Localized Twitch Responsementioning
confidence: 99%
“…Different studies have identified high concentrations of bradykinin (BK), calcitonin gene-related peptide (CGRP), nerve grown factor (NGF), interleukins 1β, IL-6, and IL-8, substance P, serotonin (5-HT), norepinephrine, and tumor necrosis factor-α (TNF-α) in active TrPs when compared with latent TrPs or control points [ 20 , 21 , 22 ]. However, some studies reported the presence of both nociceptive (hyperalgesia) and non-nociceptive (allodynia) sensitivity at the TrP area, indicating an overlap or mixed-pain phenotype [ 23 , 24 , 25 ].…”
Section: Phenotyping Myofascial Trigger Point Painmentioning
confidence: 99%
“…An important differentiation is that the nociceptive phenotype is characterized by primary hyperalgesia (i.e., hypersensitivity in the painful/affected region and appropriate to the pain-inducing stimulus), whereas nociplastic pain is characterized by secondary hyperalgesia (i.e., hypersensitivity within and outside the painful/affected region and by a greater than expected perception of pain in response to a given stimulus). Several studies have shown that myofascial pain mainly exhibits pressure pain hyperalgesia in the affected area [ 20 , 21 , 22 , 23 , 24 , 25 ]. Hyperalgesic and allodynic responses can be present in distant pain-free areas in some individuals.…”
Section: Clinical Criteria/grading System For Pain Phenotyping Of Myo...mentioning
confidence: 99%
“…Trigger points are painful spots within taut bands of skeletal muscles that produce local and referred pain either spontaneously or upon stimulation [ 15 ]. Meng et al found that TrPs contribute to central sensitization and cause plastic changes within nociceptive pathways [ 16 ]. A previous study reported that TrPs are common in the temporal and suboccipital muscles and when stimulated often reproduce a headache pain that is familiar to the patient [ 17 ].…”
Section: Introductionmentioning
confidence: 99%